The Impact of Factionalism on Political Parties in Nepal - Thapa, Santa Bahadur (International Journal of Humanities, Education, and Social Sciences, 2025)
This paper explores factionalism in Nepalese political parties and its causes and effects on party factions. Nepal’s political culture is rife with factionalism, splinter groups, and power struggles. The paper traces the historical development of factionalization from ideological conflict and personal rivalry. The paper segments society into groups based on ideology, personality, geography, and one-off issues. It analyzes the negative impact of factionalism on party discipline, stability, policymaking, and government. This paper examines the social non-linearities of leadership in factionalism and shows how their presence makes effective leadership essential to combatting factionalism's effects. This case study of major Nepalese political parties is technically an objective and practical demonstration of factionalism. A global perspective can enhance many of the firm conclusions based on case studies of factionalism within political parties in various countries. The paper suggests ways of dealing with and tackling the issue of factionalism, including the importance of keeping its internal democracy and communication and showing how to deal with elements that would not help. The paper concludes with possible driving factors behind this exclusive mirage of a political system. It suggests a few essential recommendations to subdue factionalism, like strengthening leadership, intra-party democracy, improving the legislative mechanisms, etc. It essentially places the responsibility on concern for factionalism, which can stymie effective government and dilute the moral legitimacy of democracy in Nepal.